Persianorchestia, a new talitrid genus (Crustacea: Amphipoda: Talitridae) from Gulf of Oman, Iran - Momtazi, Farzaneh; Lowry, Jim; Hekmatara, Maryam (Zootaxa, 2017)
A new genus and species, Persianorchestia nirvana gen. et sp. nov., is described from the south coast of Iran along the Gulf of Oman. The new genus is characterized by large eyes, gnathopod 1 posterior margin of carpus and propodus each with lobe covered in palmate setae, smooth posterior margin on dactylus of male gnathopod 2, a slender dactylus on pereopod 5, uropod 1 outer ramus without marginal robust setae and with apical spear-shaped setae on the rami of uropods 1 and 2. Persianorchestia is most similar to Pseudorchestoidea Bousfield, 1982.